(untitled) (Psychology Travelogs, 2023)
The article demonstrates that in the context of considering emotional intelligence as one of the types of overall intelligence, the most crucial aspect is the tasks it solves. Therefore, the use of problem situations in the process of developing emotional intelligence in youth is a mandatory condition for activating the emotional-cognitive activity of an individual. A theoretical and methodological analysis of the psychological foundations of the genesis of emotional intelligence in early youth is presented in the article, serving as the basis for the development of an author’s research concept. A theoretical model of the genesis of emotional intelligence in early youth is formulated and justified; a quantitative and qualitative analysis of the structure, levels, and features of the development of emotional intelligence in young men is conducted. A system of psychological factors, mechanisms, and regularities of the genesis of emotional intelligence in early youth is determined. In research on emotional intelligence, primary attention was given to the study of its psychological structure and relationships with other intra-personal manifestations. This tendency has led to contradictions between conceptions of the place of emotional intelligence in the structure of personality and the understanding of the structural and functional characteristics of emotional intelligence as a metacognitive construct, as well as between criteria for determining a sufficient level of emotional intelligence development for psychological development of the individual and scientifically substantiated psychological-pedagogical means of influencing the formation, functioning, and development of emotional intelligence. However, the question of the peculiarities of emotional intelligence development at different age stages of psychological development of the individual remains problematic. Problems of the genesis of emotional intelligence in youth have practically not been studied, and consequently, there is a lack of a clear understanding of the psychological conditions and specifics of emotional intelligence development in youth.